The Contemporary System of German Economic Diplomacy - R. O. Raynkhardt (Vestnik MGIMO-Universiteta, 2015)
The article deals with the description and analysis of functioning of the German national system of economic diplomacy. The author provides a brief summary of historical and economic background, stages and conditions of its development from the 1950-s to present time. He casts light upon the procedures and mechanisms of interaction between the key national economic-diplomatic agents i.e. ministries, agencies, other authorized bodies, public and private institutes outlining their usage of concrete economic, administrative and legal instruments in the course of respective policy measures. The author looks into the distinctive features which encompass the essence of the model: a two-level system with three pillars: foreign representations of the MFA, Germany Trade and Investment Agency, chambers of commerce. The above elements do not overlap each other's functions, but complement them; their functioning is based upon interministeriality and the single window concept. A special focus is made on the practice of economic-diplomatic agents, especially chambers of commerce, using private public partnership instruments. In general, notwithstanding recurring negative trends of the domestic and global business climate (oil crisis in the 1970-s, recession of the late 2000s - early 2010s) the German economy demonstrated of high resistibility to exogenous shocks compared to other economies and according to the absolute values of its macroeconomic indicators. Alongside other economic and noneconomic factors this stability can to a certain extent be explained by an efficient system of economic diplomacy. Established in the 1970s it keeps on evolving in order to stand up to new challenges. At any stage of the business cycle it constitutes a pillar of the German economy and, ultimately, of the economy of the European Union.